ENVIRONMENTAL TARGETS AND MEASURES IN THE STRATEGIES AND PROGRAMMES OF REGIONAL DEVELOPMENT IN THE CZECH REPUBLIC - Alois HYNEK; Jan TRAVNICEK (European Journal of Geography)
The presented article examines the state of environmental politics in the Czech Republic, specifically the Moravia Region. This issue area is connected to more theoretical questions of how to understand the relationship between th e environment and pol itics. Thus, after an analysis of the Czech environmental legislation, two related theoretical lenses are discussed: political ecology and environmental security. As will become clear from the discussion, the conceptual distinction which is relevant in th is context is of the link between landscape and spatiality. What follows is an outline of an original synthesizing scheme with dimensions. The second part of the article uses the abov e insights to shed light on spatial landscape ecosystems in South Moravia region of the Czech Republic. In concrete terms, environmental targets and measures of regional environmental development are scrutinized. The article is summed up in the conclusion